PENGARUH KUALITAS PELAYANAN KANTOR DEPAN TERHADAP LOYALITAS TAMU PADA HOTEL STEVIE 6 BANDUNG - SE, Derizal (MENARA EKONOMI, 2018)
Can besaid to be good orservice quality if the business is ran in accordance withwhat is expected by the company. A service can be said if the quality of services provided to satisfy customers and the expected level of sales by a company can be reached, and can measure guest loyalty. This study, entitled“Affect of Service Quality Front Office On Guest Loyalty in The Stevie 6 Hotel Bandung”. The aim of research to analyze the Affect of Service Quality Front Office On Guest Loyalty in The Stevie 6 Hotel Bandung. While research method used is descriptive method with quantitative approach to data collection through questionnaires, interviews, field observations, and a study document. The object of research here are guests staying at the Stevie Hotel 6 Bandung. The independent variable (X) is the five dimensions of service quality (tangible, Reliability, responsiveness, assurance, and empathy). While variable (Y) is the guest loyalty which has a threedimensional (repeat, retention, referral). Based on the technique of random sampling of 100 respondents obtained. The technique used is a simple linear regression technique. Results of the study showed the average value of all dimensions of service Front Office Hotel has an average of 69.07 and included in both criteria, while loyalty has an average of 79.76 and both criteria. Loyalty variables are influenced by the variable quality of service is 32,5% and the remaining 67,5% influenced by other factors not examined in this study, such as guest satisfaction.Keywords ; Service Quality, Guest Loyalty, Front Office